The human TRPA1 intrinsic cold and heat sensitivity involves separate channel structures beyond the N-ARD domain - Moparthi, Lavanya; Sinica, Viktor; Moparthi, Vamsi K; Kreir, Mohamed; Vignane, Thibaut; Filipovic, Milos R; Vlachova, Viktorie; Zygmunt, Peter M (Nature communications, 2022)
TRP channels sense temperatures ranging from noxious cold to noxious heat. Whether specialized TRP thermosensor modules exist and how they control channel pore gating is unknown. We studied purified human TRPA1 (hTRPA1) truncated proteins to gain insight into the temperature gating of hTRPA1. In patch-clamp bilayer recordings, ∆1-688 hTRPA1, without the N-terminal ankyrin repeat domain (N-ARD), was more sensitive to cold and heat, whereas ∆1-854 hTRPA1, also lacking the S1-S4 voltage sensing-like domain (VSLD), gained sensitivity to cold but lost its heat sensitivity. In hTRPA1 intrinsic tryptophan fluorescence studies, cold and heat evoked rearrangement of VSLD and the C-terminus domain distal to the transmembrane pore domain S5-S6 (CTD). In whole-cell electrophysiology experiments, replacement of the CTD located cysteines 1021 and 1025 with alanine modulated hTRPA1 cold responses. It is proposed that hTRPA1 CTD harbors cold and heat sensitive domains allosterically coupled to the S5-S6 pore region and the VSLD, respectively.
Keywords: Hot Temperature; Tryptophan; ankyrinová repetice; vysoká teplota; Thermosensing; vnímání teploty; alanin; tryptofan; TRPA1 Cation Channel; Humans; Alanine; lidé; Ankyrin Repeat; kationtový kanál TRPA1